Pengabdian Kukerta Unri Desa Pongkai : Menguak Sisi Lain Gedebok Pisang Menjadi Olahan Makanan Ringan Sebagai Produk UMKM - Muhd. Arief Al Husaini; Gematullah Gematullah; Hilyatul Hifziah; Lucky Saputra; Nesi Putri Sari; Putri Nabila; Rahmad Yandi Madani; Rizki Rahmayanti; Siti Fauziyah Nur; Zulmahdi herli; Fadilla Murni (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Banana tree is one of the plants that are easily found in Indonesia, a plant that only bears fruit once in its life. Utilization of the banana tree itself is still only on the fruit and leaves, the banana stem itself or known as the banana stem is one part of the banana tree that is not utilized. It turns out that after further investigation, part of the banana gedebog can be used as one of the processed foods in the form of chips, by giving it a variety of different flavors, such as Balado, spicy sweet or original flavors. This food preparation was made because considering the utilization of banana trees does not seem optimal, if you pay attention to the banana midrib, it will only become waste or garbage that will disappear when it rots. As a plant that only produces fruit once in its lifetime, it will feel useless if its utilization is not carried out optimally. On the other hand, the effort to use banana stems as processed food also opens up business opportunities for the people in the village. Where, the results of processed chips can be one of the business opportunities in the form of UMKM which can then be marketed both online and offline. This UMKM product in the form of processed food can then be used as added value from a village, which in the end becomes something that can be said as a village potential.